Linguistic Landscape and Place-Making Strategies in Internationalizing Islamic Higher Education: Evidence from UINSA Indonesia - Yusuf, Kamal; Sodikin, Sodikin (JOLLT Journal of Languages and Language Teaching, 2026)
The internationalization of higher education commonly examines issues related to curriculum reform, student mobility, or international partnership. However, its symbolic linguistic and spatial dimensions are rarely discussed. This article explores how the linguistic landscape and place-making strategies can help internationalizing an Islamic higher education institution. A qualitative descriptive-exploratory design was used to collect data from Universitas Islam Negeri Sunan Ampel Surabaya (UINSA), Indonesia. This study utilizes visual observation of 159 linguistic signs, survey, and the analysis of institutional documents. The results indicate that the linguistic landscape at UINSA is dominated by the monolingual (Indonesian) signs (79.87%), whereas English and Arabic are restricted and have symbolic purposes. The architecture, building nomenclature, and Islamic iconography reflect place-making strategies that are not yet fully integrated into space planning framework, multilingual policy, and international branding practices. Stakeholder involvement in the development of the linguistic and spatial international campus environment needs more attention. This article highlights the significance of balancing Islamic values with global strategies by incorporating multilingual and participatory policies that foster an inclusive, culturally grounded, and globally responsive academic environment.